The Effect of Profitability, Asset Structure on Capital Structure in Registered Chemical Sub-Sector Companies on IDX from 2018-2020 - Lita Novia Ciputri SM; Harman Malau (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out how profitability and asset structure can affect capital structure with the research target being 12 chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. Profitability and asset structure are independent variables and capital structure is the dependent variable in this study. This research uses purposive sampling technique. The data used in this study is secondary data taken from www.idx.co.id. This research uses multiple linear regression analysis model. This study obtained results that prove that profitability has a positive effect on capital structure while asset structure has a negative effect on capital structure. The coefficient of determination analysis shows that the adjusted R square value on the coefficient of determination test is 4.9%, where the remaining 95.1% is influenced by other variables. This shows that the independent variables in this study are not sufficiently influential on the capital structure because there are still many other variables that have a major influence on the capital structure.